Anatomical Variations Of The Brachial Plexus And Their Relevance In Regional Anaesthesia - Masood, Solmaz; Liza Rashid, Noor; Niaz Khan, Asma; Siddique, Amjad; Umar, Muhammad; Shahzad, Naeem (Journal of Neonatal Surgery, 2025)
Background: There is a large amount of anatomic variability in the development, division and position relative to nearby structures in the brachial plexus. Such differences may be applied to the success, initiation, and effectiveness of regional anesthetic procedures. Identification has been bettered with ultrasound but unanticipated designs still are an issue, especially with interscalene, supraclavicular and axillary blocks in anesthetic and pain management applications. Objectives: To evaluate the rate of brachial plexus anatomical variants in surgical patients who underwent upper limb regional blocks and evaluate whether such variations affect the success rate of the procedure, the time it takes to conduct the procedure, and the occurrence rate of complications. Study design: A prospective study. Place and Duration of Study: Jan 2024 to Jan 2025 in Department of Anatomy, Sheikh Zayed Medical College, Rahim Yar Khan, Pakistan Methods: An observational study was used to the patients who went to have their upper limb surgery under brachial plexus block using ultrasound. I was able to scan the plexus in its origin-level down to cord, and I noted differences in origin, branching and blood relation. Demographic, block performance time and success rate were recorded. Analysis was done generally by the use of statistical analysis, Student t test and chi square, where p< 0.05 was taken to be significant. The informed consent and ethical approval preceded the participation. Results: The sample was 130 patients (70 men and 50 women). The average age was 44.2 years and SD 12.6. Altogether 34 patients (28.3%) had anatomical variations. There were 8.3, 5.8 and 9.2 percent of prefixed plexus, postfixed plexus and variant musculocutaneous-median nerve communications. Changes in relationship to the subclavian artery were seen in 5%. The average block performance time took longer in variation cases (8.1 2.3 min) than normal anatomy (6.4 1.9 min) p = 0.002. The success rate of the overall block was 96.7%, 3 failures in the variation group needing additional use of distal nerve block. There was no significant neuro problems observed in follow- up. Conclusion: Brachial plexus anatomical variations are quite prevalent and may considerably affect the efficiency of the procedure when regional anaesthesia is provided. Ultrasound enables preparation and deployment to lessen incomplete clogging and difficulties. Familiarity with the typical deviations, attentive monitoring, and having prior preparation to further injections is necessary to maximize performance. A routine ultrasound examination of the upper limb prior to using block may play an important option of anatomical variation screening, thus achieving a positive result in regional anaesthesia.